KANDUNGAN SENYAWA AKTIF PADA JAMBLANG (Syzygium Cumini (L) Skeels SEBAGAI ANTIDIABETES: LITERATURE REVIEW ARTICLE - Himyatul Hidayah; Ermi Abriyani; Surya Amal; Reni Apria Ningsih (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia caused by defects in insulin secretion, insulin action or both. It is said diabetes mellitus if blood sugar levels exceed 150 mg/dL, where the normal limit for blood sugar is 70-150 mg/dL. Treatment with natural ingredients has low side effects if used correctly. One of the plants that has anti-diabetic activity is jamblang or often called juwet (Syzygium cumini (L.). literature was conducted using Google Scholar, Science Direct, Researchgate and PubMed which were published in 2010-2020 with keywords related to the topic